PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA FK UNDIP KAMPUS TEMBALANG SEMARANG) - Prisca Nurdiana Putri Dewantari, 10.05.51.0122 (Students Journal of Economic and Management, 2013)
Success in achieving organizational goals depends on several factors of human resources, organizational development needs to include how to improve its performance in order to achieve the vision and mission of the organization. Many factors affect employee performance, such as motivation, kepusan work and so forth. This study aims to establish how the employees performance is the better company, that company still exist and flourish in the future dating to examine the effect of motivation and job satisfaction. The research instrument used in this study qualify validity, with factor analysis. Because all the research instruments have Dalan indicator Loading factor or matrix components above 0.4; similarly KMO value or condition of sample adequacy was above 0.5. Reliability testing of the variables studied or tested keterandalannya konsistensiya, because it has a Cronbach alpha greater than 0.6. Model studies have shown the value of the coefficient of determination (Adjusted R2) of 0.928. that qualifies the goodness of fit, or the model is able to explain the variables studied. Hipostesis test results show that positive and significant effect of motivation on employee performance premises regression coefficient 0.729, significance level of 0.000, and the t value 11.677. Job satisfaction and a significant positive effect on employee performance with regression coefficient 0.256, standard sig t value 0.000 and 4.096. Keywords: leadership styles, work discipline, organizational culture, and employee performance